Adapting a National Framework to Inform Curricular Redesign Focused on Enhancing Student Clinical Competency - Andrew Bzowyckyj; Bridget Bradley; Pauline Cawley; Brandon Nuziale; Sarah White (Pharmacy, 2021)
Doctor of Pharmacy (PharmD) programs continually engage in curricular redesign to ensure practice readiness of graduates. With ever-increasing demands on clinical competency and curricular time, it is important to be intentional when determining curricular priorities and prioritize contemporary pharmacist practice. This paper describes how to adapt a national framework for pharmacotherapy curricula to emphasize the pharmacist’s role within a given topic area in order to facilitate conversations about allotting curricular time during a curricular redesign. Customized Tier descriptions based on various factors expected of student pharmacists during Advanced Pharmacy Practice Experiences (APPEs) were developed (e.g., relative autonomy of the pharmacist in managing the topic, emphasis on licensing exams, frequency with which students can expect to encounter the topic at school-specific experiential placements, and condition-specific information). Topics were also reprioritized to address regional variations in practice and ideologies. Customizing a national framework to determine program-specific considerations for prioritizing topics within the pre-APPE curriculum can help faculty and students alike maintain focus on highly critical and foundational concepts, while also making sure not to completely disregard topics of lower priority. We have proposed such a framework for programs to utilize when facilitating conversations surrounding curricular reforms and topic prioritization.